Celiac Trunk Mycotic Aneurysm: Diagnosis and Treatment of a Post-infective Endocarditis Complication. (November 2022) - Gabrielli, Daniela; Pagano, Paolo; Boni, Mariavirginia; Di Giosia, Paolo; Procaccini, Luca; Mincuzzi, Erica; Marinucci, Carlo; Rossi, Brunella; D' Emidio, Fabio
Pseudoaneurysms could be the dynamic evolution of an infectious break in the arterial wall; in the post-antibiotic era they are uncommon complication following infective endocarditis (IE) and are associated with high rates of morbidity and mortality especially for patients in whom a prompt diagnosis and therapeutic strategy are not performed. In this report, we describe a case of pseudoaneurysm of the celiac trunk developed as a complication of IE. Endovascular treatment is our first-line approach.